2018
DOI: 10.1080/15384101.2018.1467679
|View full text |Cite
|
Sign up to set email alerts
|

Mitostemness

Abstract: Unraveling the key mechanisms governing the retention versus loss of the cancer stem cell (CSC) state would open new therapeutic avenues to eradicate cancer. Mitochondria are increasingly recognized key drivers in the origin and development of CSC functional traits. We here propose the new term "mitostemness" to designate the mitochondria-dependent signaling functions that, evolutionary rooted in the bacterial origin of mitochondria, regulate the maintenance of CSC self-renewal and resistance to differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 96 publications
1
15
0
Order By: Relevance
“…It has been reported that high glucose alters the gene expression by methylation or acetylation of lysine residues on histone H3. A recent report showed the involvement of H3K36me2, H3K27me3, H3K9me2, and H3K23ac in metabolic disorder . We also show that there is increased K36 di‐methylation of histone H3 in HFD + low dose STZ‐induced diabetic conditions and this elevation was suppressed by l ‐Met‐S as well as metformin treatment.…”
Section: Discussionsupporting
confidence: 66%
“…It has been reported that high glucose alters the gene expression by methylation or acetylation of lysine residues on histone H3. A recent report showed the involvement of H3K36me2, H3K27me3, H3K9me2, and H3K23ac in metabolic disorder . We also show that there is increased K36 di‐methylation of histone H3 in HFD + low dose STZ‐induced diabetic conditions and this elevation was suppressed by l ‐Met‐S as well as metformin treatment.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, mitochondria have been shown to support the survival of dormant tumor cells after oncogene ablation, thus promoting disease relapse (32). Many of these actions attributed to mitochondria have been correlated with the impact that these organelles exert on the biology of CSCs (33). Several lines of evidence have suggested that mitochondria support stem cell traits, thus facilitating self-renewal and resistance to differentiation (2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mitochondrial morphology and fission-fusion dynamics have been implicated as determinants of cellular differentiation states. Interestingly, increased mitochondrial fission is reported to be associated with proliferation and invasiveness of cancer cells and dedifferentiation of stem cells (57,58). Because increased PHB in mitochondria is predicted to suppress fission, it is possible that the enhanced proliferation and dedifferentiation of neuroblastoma cells expressing high levels of PHB are due to nonmitochondrial functions of the protein.…”
Section: Discussionmentioning
confidence: 99%